MAKNA JALAN KAKI DITINJAU DARI PERSPEKTIF FILSAFAT DAN KESEHATAN: STUDI FENOMENOLOGIS TERHADAP CAMINO SAN GIOVANNI - Dole, Donatus (Aggiornamento, 2024)
This study aims to discover the aspects of walking participants awareness. The method used is phenomenological-descriptive. From the research, it was found that: walking means going to a certain point with a purpose; the activity of human life and using the legs given by God; the pilgrimage of life and a true walker is a person who makes meaning every time he walks. Philosophers have also described walking. Nietzsche found that any idea must be born out of the open air and free movement. Kant recognised that walking is simple, without a great mystical union with nature. While Rousseau confessed to never doing anything except walking, the countryside was where he learnt. He claimed to be incapable of thinking properly except when he walking. This research is very relevant to today's context where meaning is really needed in every physical movement. In addition, a healthy lifestyle is not only achieved with big things, but simply by walking.